STUDY OF THE CRUSTAL STRUCTURE, GEODYNAMICS AND THE EARTHQUAKE AND TSUNAMI HAZARD ASSESSMENT IN VIETNAM SEA AND ADJACENT AREAS - Que, Bui Cong; Phuong, Nguyen Hong; My Thanh, Tran Thi; Dung, Tran Tuan (Vietnam Journal of Marine Science and Technology, 2014)
In order to study the characteristics of crustal structure and geodynamics in theVietnam Sea and adjacent areas, all available data and results of survey and investigation ongeology, geotectonics and geophysics for about 50 last years have been accumulated and thecomplex and systematic methods for analysis and interpretation of data sources have been built todetermine the quantitative and detailed characteristics of horizontal and vertical layers of the Earthcrust. In the base of the comprehensive analysis of available and updated data, the map ofgeophysical fields (such as gravity, magnetic field, seismology, heat flow), bathymetry, structure ofthe main boundaries in the Earth crust, structure and geodynamic of the fault systems have beencompiled. With use of the deep crustal structure and geodynamics characteristics on the maps theearthquake source zones and their source parameters have been determined and in this base sometsunami scenarios that may be caused by these sources have been developed and calculated. Theresults of the earthquake and Tsunami hazards assessment presented in the maps of scale 1:500,000and larger scale reflect the picture of differenced earthquake and Tsunami hazard with some areasof relatively high and clear hazards in the Vietnam sea and coastal zones.